(untitled) (Journal of Oriental Studies, 2017)
Most movies based on novels by Mahfouz has unquestionable artistic value and represents the best of what was made in Egyptian cinema. The value of films is not limited to their artistic merit – they have significantly expanded the range of people, who enjoy the work of the largest Arab writer. With all the changes the novels undergone to in their adaptation, movies, mostly, give an idea of the high quality literary works. From this point of view, literalism, following the text strictly are not a drawback, because they allow demonstrating on the screen realistic picture of Egyptian life displayed in the novels. This is especially true for the novels of Cairo cycle in which their social problems were greatly attracting filmmakers. The politically topical novels, to which the filmmakers often accessed in the 70-ies, were subjected to the greatest changes of adaptation.